Attention distribution and cognitive load in a subtitled academic lecture: L1 vs. L2 - Jan-Louis Kruger; Esté Hefer; Gordon Matthew (Bern Open Publishing, 2014)
In multilingual classrooms, subtitling can be used to address the language needs of students from different linguistic backgrounds. The way students distribute their visual and cognitive resources during a lecture is important in educational design. Students have to shift their attention between sources of information of varying density and relevance. If there is redundancy between these sources, there will be competition and possible cognitive overload. This paper compares visual attention distribution between subtitles and other sources of information through eye tracking and relates this to academic comprehension and cognitive load as measured through self-report questionnaires and EEG. The study provides promising results for the use of both first and second language subtitles in academic contexts.